The multiple functions and mechanisms of long non-coding RNAs in regulating breast cancer progression - Zhang, Yongsheng; Xu, Yanjiao; Zhang, Yanping; Wang, Shoushi; Zhao, Mingqiang (Frontiers in Pharmacology, 2025)
Breast cancer (BC) is a malignant tumor that has the highest morbidity and mortality rates in the female population, and its high tendency to metastasize is the main cause of poor clinical prognosis. Long non-coding RNAs (lncRNAs) have been extensively documented to exhibit aberrant expression in various cancers and influence tumor progression via multiple molecular pathways. These lncRNAs not only modulate numerous aspects of gene expression in cancer cells, such as transcription, translation, and post-translational modifications, but also play a crucial role in the reprogramming of energy metabolism by regulating metabolic regulators, which is particularly significant in advanced BC. This review examines the characteristics and mechanisms of lncRNAs in regulating BC cells, both intracellularly (e.g., cell cycle, autophagy) and extracellularly (e.g., tumor microenvironment). Furthermore, we explore the potential of specific lncRNAs and their regulatory factors as molecular markers and therapeutic targets. Lastly, we summarize the application of lncRNAs in the treatment of advanced BC, aiming to offer novel personalized therapeutic options for patients.